Vállalkozásfinanszírozás egy konkrét példán keresztül - Kirschner Gábor Béláné (2018)
In our thesis we will outline the forms of funding enterpreneurships in Hungary based on own experience. In the first part of the essay, we will describe the enterprise itself and present the options one can take when considering to found his or her own business. We will then present the ways of grouping enterprises, and we will define the profit rate needed to achieve the desired size for micro-, small-, medium- and large enterprises. Of course all these are dependent on the nature of the business activities the actual enterprise performs. In the second part of our thesis we will present the ways of funding enterprises. Our goal is to present - through our own example based on available data - internal and external funding options. This way we can show based on both theoretical and practical experiences how an enterprise can address difficulties in funding and what advantages or disadvantages the different options have. We will ivestigate how to create an enterprise from financial perspective and what are the consequences of funding the business from external sources. Based on our research we will get to the conclusion that those enterprises, which have been active at least for a year, can rely on external funding more easily than the others. When analysing the credit markets, it is clearly visible that only the financials matter, the business activity and its impact on profit is not taken into account. In the last part we will take a look at the results, as well as the liabilities of Hungarian enterprises with special focus on the difficulties related to the duties towards the government. We will recommend to prescribe less additional costs for the enterprises, but on the other hand the consequences of not paying them should be stricter. With lower government related liabilities, the enterpreneurial mindset could be effectively encouraged, hence we would see higher revenues and profits. Analysing the return on investments it is visible that a business can be successful and profitable even if it uses external funding. Having said these, it is important to use the right opportunities and limit the reliance on external funding.